L’ARRET DES POURSUITES JUDICIAIRES PAR LA COURS PENALE INTERNATIONALE : APPLICATION A LA SITUATION DU KENYA - Oseyatoko, Marcel; KAHINDO, Trésor HAKIBA (IJRDO - Journal of Social Science and Humanities Research, 2019)
We are writing this article on the prosecution of the ICC against the current Kenyan President at the time the ICC prosecutor decided to abandon such prosecutions. We would like to know the reasons why the Prosecution had reached that point. As a result, the Kenyan authorities refused to cooperate with the court by the fact that "the non-transmission of certain important documents by the Kenyan authorities had an unfortunate impact on this case" and "hindered my ability to conduct an investigation To the end, "said the prosecutor. While the ICC has decided to stay the proceedings against Mr. Uhuru Kenyatta for the above reason, this does not prevent us from reflecting on the issues surrounding the surrender, on the arguments in favor and against the stay After briefly introducing the Court. The stakes are both legal and political to the extent that Burundi, RSA and The Gambia have begun the process of leaving the Rome Statute of the ICC. Many other African states still could follow suit.